Research on Fabrication of Flame Retardant Nanocomposite Coating to Protect Steel Structures on Epikote 240 Epoxy Resin Base with the Synergy of MWCNTs and Fly Ash - Tuan Anh Nguyen (International Journal of Chemical Engineering)
The use of industrial wastes such as thermal power plant fly ash can reduce the environmental risk. The fly ash properties are useful and can contribute to organic coatings. This paper examines a new strategy for coatings that protect steel structures from the effects of fire while enhancing mechanical properties. The aim of this study was to show that the fly ash additive can be a partial replacement for other conventional additives while also having a flame retardant effect. To study the effectiveness of the use of fly ash additives, we have sought to combine them with nanoadditives. Specifically, we study the synergy of fly ash with multi-wall carbon nanotube additives to reinforce the coating on the system: epoxy Epikote 240/ammonium polyphosphate (APP)/pentaerythritol (PER), and melamine. Content of fly ash was studied: 10 wt.% with 0.5, 1, and 1.5 wt.% of multi-wall carbon nanotubes (MWCNTs). The results prove that the synergies between fly ash and multi-wall carbon nanotubes increase the fire resistance to increase the protection of steel structures of the building. When using 10 wt.% fly ash and 1 wt.% MWCNTS, the coating can be considered as a flame retardant material with UL 94V-0 fire resistance and the limiting oxygen index of 27.2%..